Introduction to elementary particle physics - Bettini, Alessandro (Cambridge : CUP, 2014)
The second edition of this successful textbook is fully updated to include the discovery of the Higgs boson and other recent developments, providing undergraduate students with complete coverage of the basic elements of the standard model of particle physics for the first time. Physics is emphasised over mathematical rigour, making the material accessible to students with no previous knowledge of elementary particles. Important experiments and the theory linked to them are highlighted, helping students appreciate how key ideas were developed. The chapter on neutrino physics has been completely revised, and the final chapter summarises the limits of the standard model and introduces students to what lies beyond. Over 250 problems, including sixty that are new to this edition, encourage students to apply the theory themselves.
Appendix 1-6 424-435p.; Solution 436-457p.; References 458-465p.; Index 466-474p.
Keywords: Hadrons; Weak interations; Neutrinos